2021
DOI: 10.1021/acs.iecr.1c02765
|View full text |Cite
|
Sign up to set email alerts
|

Binder-Free Flexible Three-Dimensional Porous Electrodes by Combining Microstructures and Catalysis to Enhance the Performance of Lithium-Oxygen Batteries

Abstract: Metal-air batteries are promising for the next-generation energy storage because of attractive energy density, but they also face great challenges for applications. To intensify transfer and increase reaction active sites as well as decrease polarization, binder-free flexible three-dimensional porous oxygen electrodes were prepared by in situ deposition and decomposition of ZIF-67 on graphite foam (GF). Compared with GF, the modified sample has a much more stable discharge platform, lower charge/discharge pola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…The modified GF samples exhibit a distinctly larger CV area and more obvious redox peaks than those of the pristine GF. In Figure 1, there are two pairs of redox peaks: one is ascribed to the reduction peak at 0.30 V (which is attributed to the ORR or the reduction of Fe 3+ ) and the OER peak at 1.20 V, 26 and the other is related to the reduction of Ce 4+ at 0.65 V and the oxidization of Ce 3+ at 0.90 V. 47 The transformation of Ce 3+ /Ce 4+ is in favor of the reduction and evolution of oxygen. 12 In Figure 1a,c, there are no obvious ORR peaks due to the lack of oxygen gas in the Ar atmosphere, and the peak located at 0.3 V could be attributed to the reduction of Fe 3+ .…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The modified GF samples exhibit a distinctly larger CV area and more obvious redox peaks than those of the pristine GF. In Figure 1, there are two pairs of redox peaks: one is ascribed to the reduction peak at 0.30 V (which is attributed to the ORR or the reduction of Fe 3+ ) and the OER peak at 1.20 V, 26 and the other is related to the reduction of Ce 4+ at 0.65 V and the oxidization of Ce 3+ at 0.90 V. 47 The transformation of Ce 3+ /Ce 4+ is in favor of the reduction and evolution of oxygen. 12 In Figure 1a,c, there are no obvious ORR peaks due to the lack of oxygen gas in the Ar atmosphere, and the peak located at 0.3 V could be attributed to the reduction of Fe 3+ .…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Therefore, with rapid transport kinetics, these 3D carbon materials help achieve an extraordinary electrochemical performance. By graphitization of carbon felt, 3D macroporous graphitic foam is considered to be an ideal conductive scaffold on account of well-interconnected architecture, compliant mechanical properties, high electronic conductivity, and porosity ratio. , …”
Section: Introductionmentioning
confidence: 99%
“…It has a typical zeolite topological structure with abundant pores . Due to excellent chemical and thermal stability, ZIF-67 and its derivatives have potential applications in fields such as adsorption and separation, , electrode material, , biomedicine, , and catalysis. , In general, the physical and chemical properties of ZIF-67 are determined by particle morphology and size. ,, Chen et al investigated the antibacterial activity of ZIF-67 against Saccharomyces cerevisiae and found that the ZIF-67 nanocube performed better than the ZIF-67 rhombic dodecahedron, and the smaller the size of ZIF-67, the poorer the antibacterial activity. Li et al demonstrated that ZIF-67 showed adjustable CO 2 adsorption behaviors during the evolution from the 3D to 2D phase.…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, 2D graphene sheets can self-assemble to form a favorable 3D hierarchical porous architecture for the oxygen cathodes of LOBs. These features make graphene an ideal material for fabricating binder-free porous cathodes [29].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, a variety of methods have been reported for the efficient preparation of freestanding binder-free porous graphene electrodes. For example, graphene foams have been prepared as porous cathodes for LOBs by the carbonization of polymer precursors including melamine foam [28], polyacrylonitrile [29], etc. Graphene foams as porous cathodes have been also prepared via the electrochemical leavening of graphite papers [30].…”
Section: Introductionmentioning
confidence: 99%